Industrialization, Returns, Inequality - Thilo N. H. Albers; Felix Kersting; Timo Stieglitz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
How does revolutionary technological change impact wealth inequality? We turn to the mother of all technological shocks–the Industrial Revolution–and analyze its role for wealth concentration both empirically and theoretically. Based on a novel dataset on wealth shares at the level of Prussian counties, we provide causal evidence on the positive effect of industrialization on the top percentile's wealth share and the inequality among top fortunes. We show that this relationship between industrialization, wealth concentration, and tail fattening is consistent with both cross-country data on national wealth distributions and with a new individual-level dataset of Prussian millionaires. We disentangle the mechanisms underlying the observed wealth concentration and tail fattening by introducing a dynamic two-sector structure into an overlapping generations model with heterogeneous returns to capital. In particular, we study the role of sector-specific scale dependence, i.e. the positive correlation of rates of return and wealth in industry, and dynastic type dependence in returns, i.e., the gradual one-directional transition of wealth-holders from the low-return traditional to the high-return industrial sector. The simulations suggest that the combination of these two features explains about half of the total increase of the top-1% share, while the other half resulted from the general increase and higher dispersion of returns induced by the emerging industrial sector.
Keywords: D31; E21; N13; O14; 330; rates of return; wealth inequality; industrialization; technology; simulation